Are sigma receptor modulators a weapon against multiple sclerosis disease?. (November 2017) - Collina, Simona; Rui, Marta; Stotani, Silvia; Bignardi, Emanuele; Rossi, Daniela; Curti, Daniela; Giordanetto, Fabrizio; Malacrida, Alessio; Scuteri, Arianna; Cavaletti, Guido
Effective therapies for multiple sclerosis (MS) are still missing. This neurological disease affects more than 2.5 million people worldwide. To date, biological immunomodulatory drugs are effective and safe during short-term treatment, but they are suitable only for parenteral administration and they are expensive. Accordingly, academic and industrial environments are still focusing their efforts toward the development of new MS drugs. Considering that neurodegeneration is a contributory factor in the onset of MS, herein we will focus on the crucial role played by sigma 1 receptors (S1Rs) in MS. A pilot study was performed, evaluating the effect of the S1R agonist ( R )-RC33 on rat dorsal root ganglia experimental model. The encouraging results support the potential of S1R agonists for MS treatment.